KEBI JAKAN DASAR PENDIDIMN MENU JU MASYARAKAT MADANI INDONESIA - Sumarno, Sumarno (Jurnal Cakrawala Pendidikan, 2016)
The Indonesian people are now in a period of uncertain change due to the severity of the crisis facing them. ’The crisis has touched the wheels of the eco lomics, legal, and political systems and is very likely to touch also other aspects such as the socio- cultural and moral aspccts of living in a socicty, country and nation. The society is changing from a dual systcni, in which the political system (as a structure) and the social system (as the superstructure) are separated fronl each other, towards a 11cw system, the so-called ciivil society, whiich is actually still one step before Ihe elhical society. Uurilig the present period or structural change, the quality of the hunlan resources must be prepared, since they are the main components in the cultural change towards the intended civil society. If the proporlio l of educated citizens is still too small, it may be very difficult for the civil society to come into reality and even niore so Tor the ethical society. ’Thercfore, there necds to be rcorientatioli in the direction and basic policy of the national education to support the effort of the nation towards a civil society. The eduqtional reorentation involves two aspects. Firstly, the characteristics or the quality of the educated people suitable for the civils society need to be clarified and, secondly, at the macro-level there are real needs for a more democratic educational system, with hctter access to educational opportunities, equality in quality, efficiency, productivity, and employability.